Abstracts (Ofioliti, 2007)
- MESOZOIC TO PRESENT TECTONO-MAGMATIC EVOLUTION OF THE CENTRAL-WESTERN MEDITERRANEAN AREA Luigi Beccaluva and Gianluca Bianchini- THE STUDY OF ULTRAHIGH PRESSURE METAMORPHISM (UHPM) IN COLLISIONAL OROGENS AND ITS CONTRIBUTION TO THE EARTH’S SCIENCES Roberto Compagnoni- STRUCTURE OF THE SOUTHERN APENNINES: GEOLOGICAL, GEOPHYSICAL AND THERMOCHRONOLOGICAL CONSTRAINTS Stefano Mazzoli- MANTLE PROCESSES IN THE LITHOSPHERE: THE STUDY CASE OF PERIDOTITES FROM THE JURASSIC LIGURIAN TETHYS Giovanni B. Piccardo- THE NORTHERN CALABRIA HERCYNIAN CONTINENTAL LITHOSPHERIC SECTION Eugenio Piluso- PALEOGEOGRAPHIC, PALINSPASTIC AND KINEMATIC CONSTRAINTS AND SPECULATIONS ON THE SIZE OF THE LIGURIAN OCEANIC CRUST. IMPLICATIONS FOR THE CONVERGENT PHASE Gianfranco Principi* and Benedetta Treves- TECTONIC EVOLUTION OF THE CENTRAL MEDITERRANEAN FROM THE MESOZOIC TO THE PRESENT Eugenio Turco*, Antonio Schettino*, Alfonsa Milia**, Pietropaolo Pierantoni*, Fabrizio Felici* and Valeria Sbrescia- PLIO-PLEISTOCENE SANDSTONE COMPOSITION OF THE CRATI BASIN: IMPLICATIONS FOR QUATERNARY EVOLUTION M. Aiello, E. Le Pera and G. Robustelli- THE TRIASSIC METABASITES OF S. DONATO UNIT (NORTHERN CALABRIA, ITALY): PRELIMINARY PETROLOGICAL FEATURES D. Barca*, R. Cirrincione*, E. De Vuono*, P. Fiannacca**, F. Ietto* and A. Lo Giudice- CLOCKWISE P-T PATH FROM A METAPELITE OF THE CARDETO METAMORPHIC COMPLEX, ASPROMONTE MASSIF, CALABRIA. EVIDENCE FOR THE EXHUMATION OF AN HP TERRANE? R. Cirrincione, E. Fazio and A. Pezzino- SEISMIC PROPERTIES OF SILICATE AND CARBONATE ROCKS AT PRESSURE AND TEMPERATURE: THE CASE STUDY OF THE PELORITANI MOUNTAINS (NE SICILY) Cirrincione R.*, Kern H.**, Ortolano G.* ** and Punturo R.- EROSIVE PROCESSES IN THE TURBOLO RIVER CATCHMENT (NORTHERN CALABRIA) M. Conforti *, P.P.C. Aucelli**, G. Robustelli* and F. Scarciglia- FORE-ARC MANTLE PERIDOTITES AND BACK-ARC BASIN BASALTS FROM THE IZU-BONIN-MARIANA SUBDUCTION FACTORY (ODP LEGS 125 AND 195): A MODERN ANALOGUE FOR MEDITERRANEAN OPHIOLITES M. D’Antonio*, A. Zanetti°, P. Spadea**, N. Raffone*** and R. Vannucci- A LA-ICP-MS STUDY OF MINERAL PHASES OF MAFIC ENCLAVES IN THE RECENT OBSIDIAN LAVA FLOW OF LIPARI ISLAND M. Davì, R. De Rosa and D. Barca- CRUSTAL XENOLITHS IN THE DACITIC LAVAS FROM PANAREA ISLAND (AEOLIAN ISLANDS) R. De Rosa, P. Donato and E. Piluso- CLOTTED PELOIDAL MICRITE, FECAL PELLETS AND BIOMARKERS IN THE PREEVAPORITIC CALCARE DI BASE (SOUTHERN ITALY): EVIDENCE OF BITIC ORIGIN Adriano Guido*, Jérémy Jacob**, Pascale Gautret**, Fatima Laggoun-Défarge**, Adelaide Mastandre* and Franco Russo- PRELIMINARY GEOCHRONOLOGICAL DATA IN ZIRCON CRYSTALS IN METAMORPHIC ROCKS OF CONTINENTAL CRUST FROM THE FRIDO UNIT (SOUTHERN APENNINES) Salvatore Laurita*, Giacomo Prosser*, Giovanna Rizzo* and Massimo Tiepolo- TECTONOMETAMORPHIC EVOLUTION OF THE OPHIOLITIC SEQUENCES FROM NORTHERN CALABRIAN ARC (SOUTHERN ITALY) Francesca Liberi, Lauro Morten and Eugenio Piluso- THE LIGURIDE COMPLEX IN THE LUCANIAN APENNINES: THE FRIDO UNIT MELANGE Francesca Liberi and Eugenio Piluso- THE LIGURIDE COMPLEX IN THE LUCANIAN APENNINES: PETROLOGICAL AND GEOCHEMICAL CHARACTERIZATION OF THE TIMPA DELLE MURGE NON-METAMORPHIC OPHIOLITIC SEQUENCE Francesca Liberi- GEOMORPHOLOGY AND SOILS BETWEEN THE COLOGNATI AND TRIONTO RIVER CATCHMENTS (CALABRIA, SOUTH ITALY) F. Lucà*, T. Pelle*, G. Robustelli*, F. Scarmiglia**, D. Cugliari*, I. Pulice*, F. Dramis**, F. Muto*, G. Fuselli** and F. Corbi- ALPINE MULTISTAGE TECTONO-METAMORPHIC EVOLUTION OF THE SAMO AFRICO COMPLEX BASEMENT ROCKS (SOUTHERN CALABRIA, ITALY) G. Ortolano*, R. Cirrincione**, A. Pezzino* and R. Punturo- ZIRCONS TYPOLOGY AND CHEMISTRY FOR EARLY MESOZOIC CONTINENTAL REDBEDS OF THE TETHYAN RIFTED CONTINENTAL MARGINS, CENTRAL-WESTERN MEDITERRANEAN ALPINE CHAIN Francesco Perri*, Giovanna Rizzo*, Giovanni Mongelli*, Salvatore Critelli** and Perrone Vincenzo- A MULTIDISCIPLINARY STUDY OF DENUDATION PROCESSES AND LANDFORMS IN THE VRICA AREA (CALABRIA, SOUTHERN ITALY) I. Pulice, L. Leonardi, F. Scarciglia, G. Robustelli, M. Conforti, M. Cuscino and S. Critelli- PRELIMINARY DATA ON PLANKTONIC FORAMINIFER A BIOSTRATIGRAPHY NEOGENE DEPOSITS CROPPING OUT IN THE M.TE PORO AREA (CENTRAL CALABRIA) A. Rao and P. Gramigna- DIAGENESIS OF THE SCLERACTINIAN SKELETONS FROM THE UPPER MIOCENE CORAL-REEF CARBONATES, WESTERN CALABRIA, ITALY C. Romano*, C. Neri*, A. Russo**, F. Russo* and J. Stolarski- PETROGRAPHY AND GEOCHEMISTRY OF OPHIOLITIC DYKES IN THE LIGURIDE UNITS OF THE LUCANIA-CALABRIAN BOUNDARY (SOUTHERN ITALY) Maria T. Cristi Sansone, Giovanni Mongelli, Giacomo Prosser and Giovanna Rizzo- P-T AND DENSITY CONSTRAINTS ON A CHLORITE-AMPHIBOLE-PERIDOTITE (ULTEN ZONE, ITALY) Giovanna T. Sapienza, Roberto Braga, Marta Marocchi, Giuseppe M. Bargossi and Mirella Bondi- TIME-EVOLUTION OF BASALTIC MAGMA OF USTICA ISLAND ON LIGHT OF NEW GEOCHEMICAL AND PETROLOGICAL DATA M. Tripodo*, D. Barca*, G.M. Crisci*, R.Cristofolini** and R. De Rosa